Cooled radiofrequency ablation technology for painful bone tumors - Angileri, Salvatore Alessio; Granata, Giuseppe; Savoldi, Anna Paola; Rodà, Giovanni Maria; Di Meglio, Letizia; Grillo, Pasquale; Tortora, Silvia; Arrichiello, Antonio; Papa, Maurizio; Liguori, Alessandro; Ierardi, Anna Maria; De Filippo, Massimo; et al. (Acta Biomedica Atenei Parmensis, 2020)
Bone metastases are a common cause of cancer-related debilitating pain, especially when -localized in the vertebral column and not responsive to standard treatment. In such cases, various treatment options are available; among these is Radiofrequency, whose role has been rapidly growing over the past few years. In this study, we used the innovative Osteocool RF Ablation System (Medtronic) on a patient with a painful bone metastasis localized in the 5th lumbar vertebra, with encouraging results. The radiofrequency ablation of bone metastases with palliative aim represents an excellent treatment option, as it is a minimally invasive and safe procedure, and can be repeated multiple times.